Civil society efficacy, citizenship and empowerment in Africa (2016)
This paper contributes to the debate on the limited efficacy of civil society in Africa. It examines the complex interface between notions of civil society and citizenship within the context of the postcolonial state in Africa. It argues that the bifurcated character of citizenship is implicated in the inefficacy of civil society. This is underlined by the limited achievements in social citizenship, aggravated by the economic crisis and neoliberal reforms of the 1980s and 1990s as well as the politics of regime sustenance. Political disengagement, drain on the moral content of public life and diminished collective orientation of citizens, aggravated conflicts within society, thereby, promoting a democratisation of disempowerment and a disorganised civil society.